Nuclear translocation of silver ions and hepatocyte nuclear receptor impairment upon exposure to silver nanoparticles. Issue 5 (14th April 2020) - Tardillo Suárez, Vanessa; Karepina, Elizaveta; Chevallet, Mireille; Gallet, Benoit; Cottet-Rousselle, Cécile; Charbonnier, Peggy; Moriscot, Christine; Michaud-Soret, Isabelle; Bal, Wojciech; Fuchs, Alexandra; Tucoulou, Rémi; Jouneau, Pierre-Henri; et al.
Abstract : Upon exposure to non-toxic concentration of silver nanoparticles, only the ionic form of silver is found in the nucleus leading to an endocrine disruptor-like effect. Abstract : The impact on human health of long-term exposure to low doses of silver nanoparticles (AgNPs) remains understudied. Cellular studies have shown the intracellular dissolution of AgNPs within endolysosomes followed by Ag(i ) binding to biomolecular thiolate-containing molecules. However, the precise subcellular distribution of Ag(i ) and the nature of the disrupted physiological pathways remained unknown. Novel imaging approaches enabled us to visualize the trafficking of AgNP-containing lysosomes towards a perinuclear location and a nuclear transfer of Ag(i ) species with accumulation in the nucleoli. These Ag(i ) species impaired nuclear receptor activity, disrupting critical mechanisms of liver physiology in low dose exposure scenarios, thus justifying further research into defining a framework for the safe use of AgNPs.